2016
DOI: 10.1093/infdis/jiw085
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of AIDS-Defining Opportunistic Infections in a Multicohort Analysis of HIV-infected Persons in the United States and Canada, 2000–2010

Abstract: (See the editorial commentary by Furrer on pages 830-1.)Background. There are few recent data on the rates of AIDS-defining opportunistic infections (OIs) among human immunodeficiency virus (HIV)-infected patients in care in the United States and Canada.Methods. We studied HIV-infected participants in 16 cohorts in the North American AIDS Cohort Collaboration on Research and Design (NA-ACCORD) during 2000-2010. After excluding 16 737 (21%) with any AIDS-defining clinical events documented before NA-ACCORD enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
109
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(122 citation statements)
references
References 36 publications
8
109
0
5
Order By: Relevance
“…Since then, the widespread use of PCP prophylaxis with TMP/SMX and early ART have led to a substantial decline in the PCP incidence among individuals with HIV infection. Studies in the early 2000s reported an incidence of PCP among HIV-infected individuals below 1 case per 100 person-years [2-8]. Given the trend towards earlier diagnosis of HIV infection and immediate ART independent of CD4+ T cell count, the incidence of PCP in HIV patients has likely decreased further during recent years [9-12].…”
Section: Epidemiology and Risk Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, the widespread use of PCP prophylaxis with TMP/SMX and early ART have led to a substantial decline in the PCP incidence among individuals with HIV infection. Studies in the early 2000s reported an incidence of PCP among HIV-infected individuals below 1 case per 100 person-years [2-8]. Given the trend towards earlier diagnosis of HIV infection and immediate ART independent of CD4+ T cell count, the incidence of PCP in HIV patients has likely decreased further during recent years [9-12].…”
Section: Epidemiology and Risk Groupsmentioning
confidence: 99%
“…Since there is no national surveillance for PCP in the United States and other resource-rich countries, the exact number of cases is difficult to determine. While fewer HIV-infected individuals develop opportunistic infections in resource-rich settings overall, PCP is still one of the most common opportunistic infections in HIV patients in the United States, Canada, and Europe [2, 13]. It mainly affects individuals who are unaware of their HIV infection or who get diagnosed late (i.e., late presenters) or are not receiving ongoing care for HIV infection [14, 15].…”
Section: Epidemiology and Risk Groupsmentioning
confidence: 99%
“…Several factors are independently associated with occurrence of OI such as African American/Black race or Hispanic/Latino ethnicity, intravenous drug users, heterosexual HIV transmission, lower TCD4+ cell count, and higher viral load [5]. Sixteen large cohorts of HIV-infected patients were recently evaluated and reported a decrease in the incidence rates of first OIs, from 2.96 events/100 person-years in 2000–2003 to 1.45 events/100 person-years in 2008–2010 [5].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…The stabilized immune system has protected HIV infected persons from common opportunistic infections which used to be the major factor for increased morbidity/mortality and has enabled them to live longer. (9,10) Despite the proven efficacy of HAART, the risk remains high because the immune system function remains impaired in the individuals once infected by HIV. Death associated with cancer among the HIV infected has therefore remained a big challenge.…”
Section: Introductionmentioning
confidence: 99%